METAPHORS IN THE HEADINGS OF KALTIM POST NEWS - Irma Soleha (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2019)
Metaphors used in the political news published in Kaltim Post Daily News are analyzed in this study.  The objectives of the analysis are to see kind of metaphors and their intended meaning in the context of news.  Content analysis is used for the design in this study.  Data are collected from available news published in October to November 2008.  Criteria of metaphors as proposed by Wahab (1995) are used for analysis.  This study identified two kinds of metaphors among three kinds proposed by Wahab (1995).  The first kind is nominative metaphors used as a subject of a sentence.  The second kind is a predictive metaphor used for a predicate of a sentence.  In the context of lead presentation in of news in publication, the use of nominative and predicative metaphors are relevant to the uses of precise diction in the limited space of publication.               Keywords:  metaphors, predicative, nominative, news, lead.